Impact of Microclimate on Fatty Acids and Volatile Terpenes in "Kerman" and "Golden Hills" Pistachio (Pistacia vera) Kernels. Issue 7 (17th June 2019) - Polari, Juan J.; Zhang, Lu; Ferguson, Louise; Maness, Niels O.; Wang, Selina C.
Abstract: Pistachio is an economically important nut crop in California. Since temperature variations among geographical locations can influence biochemical processes during fruit development, it is of great relevance to understand the impact of growing area over the components that define the nutritional and sensory characteristics of pistachio nuts. Changes in moisture, fat content, fatty acid composition and volatile terpenes were studied during kernel development for "Kerman" and "Golden Hills" varieties in two different California Central Valley microclimates, Lost Hills and Parlier. Moisture content decreased from July to September for both cultivars at both locations. Kerman had a higher moisture content at both locations compared with Golden Hills. Harvest time affected fat content only for Kerman, where the values increased drastically from 21‐July to 4‐Aug, then remained constant. Golden Hills' fat content remained constant during the period of the study. The main fatty acid in pistachio oil is oleic acid (46% to 59%), followed by linoleic acid (26% to 36%) and palmitic acid (11% to 16%). C16:0, C16:1, C18:2, and C18:3 decreased with harvest time, while C18:1 increased. α‐Pinene was the most concentrated volatile among the cultivars and locations. It decreased with harvest time for both cultivars at both locations, ranging from 105 to 2464 mg/kg. At harvest, Golden Hills and Kerman at Parlier both had higher concentrations of α‐pinene than the two cultivars at Lost Hills. Our results demonstrate that microclimate affects biosynthesis of fatty acids and terpenes in pistachio kernels, the main compounds responsible for pistachio nutritional and sensory characteristics.